Quality of life and mental health of women who had cardiac disease in pregnancy and postpartum - Jane Hutchens; Jane Frawley; Elizabeth A. Sullivan (BMC, 2022)
Abstract Purpose Cardiac disease is a leading cause of maternal morbidity and mortality yet there is limited research on women's experiences and quality of life (QoL) outcomes. The aim of this study is to explore the general and health-related QoL (HRQoL) and mental health outcomes for women who have experienced cardiac disease in pregnancy and the first 12 months postpartum (CDPP). Methods This exploratory descriptive study recruited 43 women with acquired, genetic and congenital CDPP. Patient reported outcomes measures (PROMs) used were: WHOQoL-Bref, a Kansas City Cardiac Questionnaire (KCCQ), the Depression, Anxiety and Stress Scales-21 (DASS-21), the Cardiac Anxiety Questionnaire (CAQ) plus newly developed questions. Results Women reported low health satisfaction (51.7/100), physical health (55.2/100) and low HRQoL (63.1/100). Women had clinically significant scores for depression (24%), anxiety (22%) and stress (19.5%) (DASS-21) and 44.5% scored at least moderate anxiety on the CAQ. Most women (83.7%) were advised to avoid pregnancy which 88.9% found "upsetting" to "devastating"; 10.0% were offered counselling. Most women were concerned about reduced longevity (88.1%), offspring developing a cardiac condition (73.8%), and the limitations on enjoyment of life (57.1%). Women missed medical appointments due to cost (25.03%) and difficulty arranging childcare (45.5%). Conclusion The majority of women reported inadequate information and counselling support, with women with CDPP having sustained impaired QoL and mental health outcomes. The new and modified questions relating to mothering and children reflected the primacy of mothering to women's identity and needs.